Teaching Management And Sustainable Utilization Of Water Resources At Infant Level In Primary Schools In Zimbabwe: Challenges And Opportunities - Saiden, Thondhlana; Remigios , Mangizvo V. (Advances in Social Sciences Research Journal, 2019)
Water has become an inadequate resource as a result of population and economic growth, climate change, pollution and other challenges. This is impacting on social, economic and environmental wellbeing. Education about water issues at all levels is pertinent to equip people with knowledge, skills and values of its management and sustainable utilization. Young children have a tendency of wasting water because of lack of knowledge of its management and sustainable utilization. The study aimed at establishing how knowledge, skills and attitudes of the management and sustainable utilization of water resources were being transmitted to school pupils in the infant grades in primary school. Furthermore the study wanted to find out the extent to which the curriculum content addressed the management and sustainable utilization of water resources. The study was conducted in the infants section of primary schools in the City of Gweru. It was qualitative in nature and it employed document analysis, in-depth interviews and questerviews to gather data. The sample of seven teachers in the infant section was purposively selected as these were the people with the requisite information. The study established that the infant syllabi has inadequate content for the management and sustainable utilization of water resources. The education system in Zimbabwe has not put in place mechanisms and strategies to pass on information to the young learners. Teachers have not been capacitated to deal with this aspect of the curriculum. The methods used in schools to inculcate the content are suitable for the age levels. The study concluded that the content and teaching of management and sustainable utilization were not adequate. The materials to complement the teaching were relevant. The study recommends the assessment methods need to be practical so as to establish the attitudes and skills acquired and that adequate content has to be injected into the curriculum.